Between Vision and Obedience - Rethinking Theological Epistemology : Theological Reflections on Rationality and Agency with Special Reference to Paul Ricoeur and G.W.F. Hegel. - Ille, George (James Clarke & Co, 2014)
The present study seeks to respond theologically to current discussions about ideas of self from the perspective of God's action in and towards the world. Its aim is to trace a view of rationality that follows the drama of God's engagement with the world, thus involving dying and resurrection, ascesis and abundance, suffering witness and Eucharistic communion. Since, as Calvin notes, knowledge of God and knowledge of self are intimately bound together, this exercise of discerning the shape of a theological rationality in the present arena of competing promises of meaning and truth is carried o.